2023
DOI: 10.1002/ca.24091
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in skeletal muscle fiber types: A meta‐analysis

Abstract: Biopsies have been acquired from living men and women to determine proportions of Type I (slow‐twitch) and II (fast‐twitch) skeletal muscle fibers since the 1970s. Sex differences have been assumed but the literature has not been submitted to meta‐analysis. Here, the aim was to generate effect sizes of sex differences in muscle fiber cross‐sectional areas, distribution percentages, and area percentages. Data from 2875 men and 2452 women, who participated in 110 studies, were analyzed. Myofibrillar adenosine tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 80 publications
1
7
1
3
Order By: Relevance
“…Functions with multiple arrows had varied responses. of oxidative type I fibers than men (Nuzzo, 2024) and highly oxidative muscle tissue has been found to release more EVs and release EVs with differing miRNA contents than glycolytic tissue (Estrada et al, 2021;Kargl et al, 2023;Nie et al, 2019). This is slightly counter to our findings as only men had an increase in EV abundance following training, but it may have contributed to the miRNA differences.…”
Section: Evs After 12 Weeks Of Training In Men But Not Womencontrasting
confidence: 99%
“…Functions with multiple arrows had varied responses. of oxidative type I fibers than men (Nuzzo, 2024) and highly oxidative muscle tissue has been found to release more EVs and release EVs with differing miRNA contents than glycolytic tissue (Estrada et al, 2021;Kargl et al, 2023;Nie et al, 2019). This is slightly counter to our findings as only men had an increase in EV abundance following training, but it may have contributed to the miRNA differences.…”
Section: Evs After 12 Weeks Of Training In Men But Not Womencontrasting
confidence: 99%
“…This result is in partial agreement with our findings, as we also observed that females had a lower frequency in the VL but similar in the VM compared to males. One possible explanation for this finding is the greater distribution of fast-twitch muscle fibers (which have a higher muscle fiber conduction velocity) in males compared to females, mainly in the VL [42].…”
Section: Discussionmentioning
confidence: 98%
“…The different representation of Type I/IIa and type IIb muscle fibers in males and in females could help explaining the sex dimorphism that we observed in the correlation between HDL and SMI. In fact, type I muscle fibers are more represented in female than in male skeletal muscle making the role of muscle fibers in lipid metabolism potentially more relevant in females than in males [ 45 , 46 ] and the consequence of obesity-induced muscle metabolic dysfunction more severe in females than in males. It should also be considered that the higher representation of type I fibers in female skeletal muscles increases their ability to accumulate intracellular lipids and, potentially, to undergo lipid-mediated cell damage [ 47 ].…”
Section: Discussionmentioning
confidence: 99%